2022
DOI: 10.3390/f13122039
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Water Conservation Function of Hulunbuir Forest–Steppe Ecotone Respond to Climate Change and Land Use Change?

Abstract: The scarcity of water resources is becoming a global focus, and water conservation has become one of the most crucial service functions in the water security and sustainable development of ecosystems. Hulunbuir forest–steppe ecotone, as an important water conservation area in the northeastern provinces of China, plays an irreplaceable role in Northeastern China. However, the water yield and water conservation are rarely understood in the ecotone. In this study, the InVEST model was employed to analyze the spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In order to make it easier to grasp both national trends and potential areas for growth, Mengistu et al (2023) analyzed the possibilities for integrated planning with a special emphasis on comprehensive planning and water management planning [7]. The relationship between land use and water management may be strengthened by action at all levels, including local implementation, regional cooperation, and statewide legislation [60][61][62].…”
Section: Integrated Land Use and Water Management Planningmentioning
confidence: 99%
“…In order to make it easier to grasp both national trends and potential areas for growth, Mengistu et al (2023) analyzed the possibilities for integrated planning with a special emphasis on comprehensive planning and water management planning [7]. The relationship between land use and water management may be strengthened by action at all levels, including local implementation, regional cooperation, and statewide legislation [60][61][62].…”
Section: Integrated Land Use and Water Management Planningmentioning
confidence: 99%
“…The process by which an ecosystem stores and holds onto water within a specific time and space range is referred to as water conservation (José, 2017). Earlier studies have indicated that the two main factors affecting water conservation are precipitation and land use (Ma et al, 2022;Qin et al, 2023;Xu et al, 2022). Water production can be influenced by precipitation modifications, which in turn limit ecosystems' ability to conserve water (Pei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%